Brain Nrf2 pathway, autophagy, and synaptic function proteins are modulated by a short-term fructose feeding in young and adult rats. (2nd April 2020) - Spagnuolo, Maria Stefania; Bergamo, Paolo; Crescenzo, Raffaella; Iannotta, Lucia; Treppiccione, Lucia; Iossa, Susanna; Cigliano, Luisa
Abstract : Objectives: A strong rise of the fructose content in the human diet occurred in the last decade, as corn syrup is widely used as a sweetener for beverages and processed food. Since young people make a widespread consumption of added sugars, we evaluated the effects of a two weeks fructose-rich diet on brain redox homeostasis, autophagy and synaptic plasticity in the cortex of young and adults rats, in order to highlight the early risks to which brain is exposed. Methods and Results: Short-term fructose feeding was associated with an imbalance of redox homeostasis, as lower amount of Nuclear factor (erythroid derived 2)-like 2, lower activity of Glucose 6-phosphate dehydrogenase and Glutathione reductase, together with lower Glutathione/Oxidized Glutathione ratio, were found in fructose-fed young and adult rats. Fructose-rich diet was also associated with the activation of autophagy, as higher levels of Beclin, LC3 II and P62 were detected in cortex of fructose-fed rats. A diet associated decrease of synaptophysin, synapsin I, and synaptotagmin I, was found in fructose-fed young and adult rats. Interestingly, BDNF amount was significantly lower only in fructose-fed adult rats, while the level of its receptor TrkB decreased in both groups of treated rats. A further marker of brain functioning, Acetylcholinesterase activity, was found increased only in fructose-fed young animals. Conclusion: Overall, our findings suggest that young rats may severely suffer from the deleterious influence of fructose on brain health as the adults and provide experimental data suggesting the need of targeted nutritional strategies to reduce its amount in foods.